If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 5) = -150 Reorder the terms: x(5 + x) = -150 (5 * x + x * x) = -150 (5x + x2) = -150 Solving 5x + x2 = -150 Solving for variable 'x'. Reorder the terms: 150 + 5x + x2 = -150 + 150 Combine like terms: -150 + 150 = 0 150 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-150' to each side of the equation. 150 + 5x + -150 + x2 = 0 + -150 Reorder the terms: 150 + -150 + 5x + x2 = 0 + -150 Combine like terms: 150 + -150 = 0 0 + 5x + x2 = 0 + -150 5x + x2 = 0 + -150 Combine like terms: 0 + -150 = -150 5x + x2 = -150 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = -150 + 6.25 Reorder the terms: 6.25 + 5x + x2 = -150 + 6.25 Combine like terms: -150 + 6.25 = -143.75 6.25 + 5x + x2 = -143.75 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = -143.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) | | 2(3a+1)=12+2(4a+3) | | 8-5x-4=-6x+6 | | 3m-4=20 | | 25*x^2-16*x^2= | | Y+14=10 | | x^0+1=0 | | 14x-12+30=4 | | 8z-9=90 | | 2z+y=4z+11 | | z=6z+18 | | 8z-9=1z+9 |